I numeri dell’Io Immaginario neoliberale e quantificazione del sé. - Luca Mori (Im@go. A Journal of the Social Imaginary, 2018)
Numbers of the Ego. Neoliberal imaginary and quantified self. After having recognized competition as the “hidden king” of contemporary neoliberal imaginaries, the paper will try to focus on the impact this specific cultural order is having on the lives of individuals. To narrow down the field, a small but representative empirical phenomenon will be taken into consideration: that is the so-called quantified self (hereafter QS). This expression refers to the use of different kinds of technologies to collect and resemble quantitative data flows on individual physical and psychological states and behavioural activities. One could think of QS as a way to increase individual awareness of personal potential and limitations in order to be better competitors in the neoliberal society. But this is just one part of the story. What is argued is that QS implies a radically different kind of subjectivation process, one that basically dispenses with the social relations, and finds its relational pole in the self image produced by the flows of data.